Interspecific competition, growth and productivity of maize and pea in intercropping mixture - Chandra Dhar, Probir; Abdul Awal, M.; Satu Sultan, M.; Masud Rana, M.; Sarker, Aniruddha (Scientific Journal of Crop Science, 2013)
A field trial was conducted to study the interspecific competition, growth and productivity of maize and pea in intercropping mixture in the department of Crop Botany, Bangladesh Agricultural University from November 2009 to April 2010. In this intercrop association, maize was considered as main crop and pea as intercrop. The experiment comprised of four treatments namely, (i) sole maize, (ii) sole pea, (iii) single row intercropping mixture (1M:1P i.e. single row of maize followed by single row of pea), and (iv) double row intercropping mixture (1M:2P i.e., single row of maize followed by double rows of pea). Dry matter accumulation in cob/pod of each population plants was the maximum in sole cropped plants while that was found minimum in 1M: 2P intercropped plants especially for pea while 1M: 1P intercropped plants ranked intermediate. The 1M:2P combined maize and pea mixture produced maximum seed yield (7.82 t ha-1) which was about 10, 28 and 47% higher yield than the yield obtained from 1M:1P combined mixture stands (7.04 t ha-1), sole maize (5.65 t ha-1) and sole pea (4.15 t ha-1), respectively. The single and double row combined intercropping mixtures gave the highest land equivalent ratio (1.31 and 1.47) and area time equivalent ratio (1.33 and 1.25, respectively). In both 1M: 1P and 1M: 2P intercropping mixtures, maize population exhibited strongly higher competition over pea. The 1M: 1P and 1M: 2P intercropping mixtures generated 1.44 and 1.71-fold higher maize equivalent yield as compared to the yield obtained from maize alone.